1999
DOI: 10.1017/s0007485399000322
|View full text |Cite
|
Sign up to set email alerts
|

Cytotaxonomic studies of Encarsia Förster (Hymenoptera: Aphelinidae)

Abstract: A cytotaxonomic study was carried out on 13 species of Encarsia Förster, known to parasitize aleyrodids and diaspidids. The chromosomes varied greatly both in number and morphology, with E.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 12 publications
2
39
1
1
Order By: Relevance
“…Observations of female metaphase preparations (n4100) were consistent with a previous study (Baldanza et al, 1999), which showed, through chromosome banding techniques, that E. hispida females are diploid with karyotype 2n ¼ 10. The flow cytometry analysis ruled out the possibility that male tissue was a mosaic of haploid and diploid cells; we observed no notable differences between the nuclear DNA content of females and males (Figure 2) and thus we conclude that both sexes are entirely diploid.…”
Section: Giorgini Et Alsupporting
confidence: 88%
See 1 more Smart Citation
“…Observations of female metaphase preparations (n4100) were consistent with a previous study (Baldanza et al, 1999), which showed, through chromosome banding techniques, that E. hispida females are diploid with karyotype 2n ¼ 10. The flow cytometry analysis ruled out the possibility that male tissue was a mosaic of haploid and diploid cells; we observed no notable differences between the nuclear DNA content of females and males (Figure 2) and thus we conclude that both sexes are entirely diploid.…”
Section: Giorgini Et Alsupporting
confidence: 88%
“…These results are, to the best of our knowledge, the first report of diploid males associated with symbiont infection in the Chalcidoidea, where the greatest number of records of parthenogenesis induction by symbionts occurs. In addition, diploid males have never been found in the genus Encarsia where the occurrence of haploid males is the rule in all sexual species studied so far (Hunter et al, 1993;Baldanza et al, 1999). Aside from our findings in E. hispida, only two examples of diploid males are known in the hymenopteran groups where the genetic mechanism of single-locus complementary sex determination (sl-CSD) is absent (Stille and Darving, 1980;Dobson and Tanouye, 1998).…”
Section: Discussionsupporting
confidence: 42%
“…In Hymenoptera, the number of NORs varies from 2 to 19 in diploid karyotypes, however, the majority of species has 2 NORs (PALOMEQUE et al 1988;HIRAI et al 1994HIRAI et al , 1996LORITE et al 1997;BALDANZA et al 1999;BRITO-RIBON et al 1999;present paper). The whole spectrum occurs in the ant genus Myrmecia (Formicidae), which is characterized by very diverse chromosome numbers with the highest value of 2n=76.…”
Section: Revealing Nors By Silver and Fluorochrome Cma 3 Stainingmentioning
confidence: 61%
“…The three species referred to Tenthredo differ from each other in NOR location. Similarly, in the genus Encarsia (Hymenoptera, Aphelinidae), two closely related species sharing the same chromosome number and similar chromosome morphology were found to differ in the NOR bearing chromosomes (BALDANZA et al 1999).…”
Section: Revealing Nors By Silver and Fluorochrome Cma 3 Stainingmentioning
confidence: 95%
See 1 more Smart Citation